2022
DOI: 10.1039/d2cp01158a
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise dissociation of ion pairs by water molecules: cation-dependent separation mechanisms between carboxylate and alkali-earth metal ions

Abstract: Microhydration of ion pairs provides a detailed picture of ion dissociation. Such a combined experimental and theoretical study revealed the dissociation mechanisms of carboxylate paired with either calcium or barium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Among the minor changes in this series, the general blue shift of v cooÀ as results from the motion away from the cation in full contact, induced by hydration by an increasing number of water molecules as already observed in the case of Ca 2+ . 31,32 The blue shift of d HOH between n = 6 and n = 9 suggests the formation of the second hydrated shell from the analogy to the infrared spectra of [CD 3 CD 2 COOCa] + (H 2 O) n (n r 12), 31 in which the ion pair COO À Á Á ÁCa 2+ keeps the full contact structure. From these infrared spectra, we conclude that Mg 2+ is in full contact with COO À in [CH 3 COOMg] + (H 2 O) 6 , and thus that the solvent-separated ion pair (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the minor changes in this series, the general blue shift of v cooÀ as results from the motion away from the cation in full contact, induced by hydration by an increasing number of water molecules as already observed in the case of Ca 2+ . 31,32 The blue shift of d HOH between n = 6 and n = 9 suggests the formation of the second hydrated shell from the analogy to the infrared spectra of [CD 3 CD 2 COOCa] + (H 2 O) n (n r 12), 31 in which the ion pair COO À Á Á ÁCa 2+ keeps the full contact structure. From these infrared spectra, we conclude that Mg 2+ is in full contact with COO À in [CH 3 COOMg] + (H 2 O) 6 , and thus that the solvent-separated ion pair (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It faithfully reproduces the experimental spectra and has recently been practiced by several researchers. 52–55 The geometrical analysis of the PNO:DMTCCP complex (Fig. 3a) revealed that two (O⋯C 4/10 ) of the four d O⋯C and ∠O⋯CN are 293 pm and 107°, respectively, whereas the other two (O⋯C 6/8 ) d O⋯C and ∠O⋯CN are 312 pm and 114°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It faithfully reproduces the experimental spectra and has recently been practiced by several researchers. [52][53][54][55] The geometrical analysis of the PNO:DMTCCP complex (Fig. 3a C^N are 312 pm and 114°, respectively.…”
Section: Structure and Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 -tagged ions were irradiated in the cold trap with a tunable IR laser (LaserVision: OPO/OPA). Hydrogen molecules were detached from the cluster ions when the wavenumber of the IR laser was resonant with a vibrational transition of the cluster ions. , The photofragments were extracted linearly and detected by linear TOF-MS. The photofragment ion signals from a dynode converter detector of TOF-MS were amplified 10 times using a preamplifier and recorded on a fast digitizer.…”
Section: Methodsmentioning
confidence: 99%